Examining Certification Values of Certified Employees in Indonesiaâ€™s Tourism Industry - Marannu Eppang, Buntu; Puad Mat Som, Ahmad (International Journal of Engineering and Technology, 2018)
The study of values of certification is lacking in the tourism industry. This study is an exploratory study based on the perception of tourism workforce in tourism industry in Indonesia as a developing country. Initially, a descriptive analysis was used to provide professional's viewpoints about values of certification. Later a confirmatory factor analysis was employed to explore parameters which construct values of certification in the tourism industry. The result of the study shows that parameters of intrinsic values dominate the construct of values of certification. This finding implies that the implementation of values of certification is beyond the expectation and there is a need to enforce regulations related to values of certification in developing country.Â Â